The cultural policy in Italy and the innovations of the XXI century - Niglio, Olimpia (Universitat Politècnica de València, 2018)
The paper analyzes the development of the first experiences of the sixteenth century cultural policy in Italy until the beginning of the twenty-first century with the institutional reform initiated by the Minister Dario Franceschini. In the pre-unification State it has been many important contributions of several local rulers who imposed conservation policies to prevent the dispersal of works of art. After the unification of Italy (1861) the laws of protection of the national heritage have helped to initiate the first important initiatives that have developed in practice only at the end of the twentieth century. Great institutional innovations and regulatory activated in the twenty-first century and of which this paper provides some important insights and deepening.